Las Panateneas: un ejemplo de relaciones sociales a través de la fiesta - Nuez Pérez, María Eugenia De La (Gerión. Revista de Historia Antigua, 2009)
In ancient Greece, the festivals were the most visible link between the deity and the citizens. The Religion was another element of the culture thus, the social or political changes are reflected in the festivals. Panathenaia are a privileged festival because we can see this changes in the socials links through the variations in the ritual, specially in V B. C. the period which I will studied in this paper.
Keywords: Panathenaia; Athens; Social links; Religion; Festivals